Immune Protection of SIV Challenge by PD-1 Blockade During Vaccination in Rhesus Monkeys - Pan, Enxiang; Feng, Fengling; Li, Pingchao; Yang, Qing; Ma, Xiuchang; Wu, Chunxiu; Zhao, Jin; Yan, Hongbin; Chen, Rulei; Chen, Ling; Sun, Caijun (Frontiers in Immunology, 2018)
Though immune correlates for protection are still under investigation, potent cytotoxic T lymphocyte responses are desirable for an ideal HIV-1 vaccine. PD-1 blockade enhances SIV-specific CD8+ T cells. However, little information has been reported about how it affects the immunogenicity and protection of prophylactic SIV vaccines in nonhuman primates. Here, we show that PD-1 blockade during vaccination substantially improved protective efficacy in SIV challenged macaques. The PD-1 pathway was blocked using a monoclonal antibody specific to human PD-1. Administration of this antibody effectively augmented and sustained vaccine-induced SIV-specific T cell responses for more than 42 weeks after first immunization in rhesus monkeys, as compared with SIV vaccination only. Importantly, after intrarectally repeated low-dosage challenge with highly pathogenic SIVmac239, monkeys with PD-1 blockade during vaccination achieved full protection against incremental viral doses of up to 50,000 TICD50. These findings highlight the importance of PD-1 blockade during vaccination for the development of HIV vaccines.